Ecología, manejo y aprovechamiento sustentable de la uña de gato (Uncaria guianensis (Aublet) y Uncaria tomentosa (Willd.) D.C) en comunidades Tikuna del sur de la Amazonia colombiana (2020)
Cat's claw species are recognized for their use in the traditional medicine of Amazonian communities and their commercial potential in the pharmaceutical industry, due to the preventive and palliative pharmacological properties. The interest in the commercialization of these species, especially of U. tomentosa, has led to intensive extraction in primary forests without taking into account aspects of sustainability. This situation makes evident the need to establish guidelines for an adequate use of Uncaria guianensis and U. tomentosa, taking into account ecological, social and cultural aspects. The general objective is to determine the use and management of cat's claw species in Tikuna indigenous communities, which, articulated with information on ecological, botanical and edapho-biological conditions, contribute to the knowledge of alternatives for a possible sustainable use of those species in the southern Colombian Amazon. An interdisciplinary study with four methodological phases was proposed for this aim: local knowledge of cat's claw, identification of species, landscapes and soils, laboratory work and use of the species. The results showed that Uncaria species do not have a homogeneous distribution in the south of the Colombian Amazon and that their propagation is favored in intervened areas of successional forests. U. guianensis has greater abundance and distribution in the territory that U. tomentosa, because this species was found in floodplains and highlands, with an abundance of 1,1 individuals/hectare y 0,4 individuals/hectare, respectively. Also, it is considered by Tikuna´s communities as a higher valuable medicinal resource in comparison with the other species. It was found that traditional management is mainly due to natural regeneration in clearings of secondary forests; and then with the planting in growing areas. These communities possess the botanical knowledge of cat's claw species, as well as growth areas, weed control and bark extraction methods. However, agroecological management should be strengthened with knowledge about species inventory, multiplication of plant material, agroforestry associations and raw material processing. This research provide additional information on the Uncaria species, which will lead to socially and economically viable management practices, as well as ecologically more appropriate in the Amazon region